PADANAN YO BAHASA JEPANG DALAM BAHASA MELAYU RIAU DIALEK RANTAU KUANTAN DI DESA PULAU BANJAR KARI - Ayuningsih, Atika; Aibonotika, Arza; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study discussed the equivalent of the final particle yo in Japanese as a function to make listeners aware of things that are not known by listeners in Riau Malay dialect Rantau Kuantan in Pulau Banjar Kari Village. The purpose of this study was to determine the equivalent of the final particle yo in Japanese in Riau Malay dialect of Rantau Kuantan in Pulau Banjar Kari Village. The method that used in this research is descriptive qualitative. The data was obtained from an original informant from Pulau Banjar Kari Village who did a role play in Riau Malay dialect Rantau Kuantan according to a simple Japanese conversation with the final particle yo which has been translated into Indonesian. The result of this research is that there are 4 variations of endings from 2 different conversational situations that appear in Riau Malay dialect of Rantau Kutan in Pulau Banjar Kari Village. Of the four variations of the suffix the most dominant used by the informants was the suffix ha as many as 5 informants. The suffix ha according to the informant is the suffix that is most often used when trying to tell or alert someone to something that the listener is not aware of.Keywords: equivalent, shuujoshi yo, Riau Malay dialect Rantau Kuantan, Pulau Banjar Kari Village